Upcycling Plastic Waste for the Development of Construction Materials - Carbonnel-Torralbo, A; Perez-Herrera, H; Gavilanes-Ruiz, D; Escobar-Carrillo, D (Firenze University Press, 2021)
Consideration of plastic waste as a secondary raw material obtainable by means of upcycling presents fresh possibilities in the search for new construction and architectural materials. This paper demonstrates the possibility of recycling thermoplastic polyethylene terephthalate (PET) and the potential for enhancement of its properties through the incorporation of nanoparticles. The design of materials by means of managed complexity involving processes of materialisation and configuration is explored by processing film from recycled plastic and their subsequent assessment as a possible semi-finished product with photocatalytic potential. © 2021 Firenze University Press.
Keywords: Upcycling; Photocatalysis; Materials design; Plastic recycling; Nanotechnology